Leadership under fire : the challenging role of the Canadian university president - Paul, Ross H. (McGill-Queen's University Press, 2011)
"Combines leadership theory, interviews with eleven of Canada's most successful presidents, and thirty-five years of personal experience to shed light on the complexity and importance of leading a university and identifies some of the critical challenges and opportunities facing Canadian universities today."--Jacket